Congruence of patient‐ and clinician‐reported toxicity in women receiving chemotherapy for early breast cancer. Issue 13 (21st April 2020) - Nyrop, Kirsten A.; Deal, Allison M.; Reeve, Bryce B.; Basch, Ethan; Chen, Yi Tang; Park, Ji Hye; Shachar, Shlomit S.; Carey, Lisa A.; Reeder‐Hayes, Katherine E.; Dees, Elizabeth C.; Jolly, Trevor A.; Kimmick, Gretchen G.; et al.
Abstract : Background: The National Cancer Institute's Patient‐Reported Outcomes Version of the Common Terminology Criteria for Adverse Events, collected alongside the clinician‐reported Common Terminology Criteria for Adverse Events, enables comparisons of patient and clinician reports on treatment toxicity. Methods: In a multisite study of women receiving chemotherapy for early‐stage breast cancer, symptom reports were collected on the same day from patients and their clinicians for 17 symptoms; their data were not shared with each other. The proportions of moderate, severe, or very severe patient‐reported symptom severity were compared with the proportions of clinician‐rated grade 2, 3, or 4 toxicity. Patient‐clinician agreement was assessed via κ statistics. Chi‐square tests investigated whether patient characteristics were associated with patient‐clinician agreement. Results: Among 267 women, the median age was 58 years (range, 24‐83 years), and 26% were nonwhite. There was moderate scoring agreement (κ = 0.413‐0.570) for 53% of symptoms, fair agreement for 41% (κ = 0.220‐0.378), and slight agreement for 6% (κ = 0.188). For example, patient‐reported and clinician‐rated percentages were 22% and 8% for severe or very severe fatigue, 41% and 46% for moderate fatigue, 32% and 39% for mild fatigue, and 6% and 7% for none. Clinician severity scores were lower for nonwhite patients in comparison with white patients for peripheral neuropathy, nausea, arthralgia, and dyspnea. Conclusions: Although clinician reporting of symptoms is common practice in oncology, there is suboptimal agreement with the gold standard of patient self‐reporting. These data provide further evidence supporting the integration of patient‐reported outcomes into oncological clinical research and clinical practice to improve monitoring of symptoms as well as timely interventions for symptoms. Abstract : Although clinician reporting of symptoms is common practice in oncology, there is suboptimal agreement with the gold standard of patient self‐reporting. These data provide further evidence supporting the integration of patient‐reported outcomes into oncological clinical research and clinical practice to improve monitoring of symptoms as well as timely interventions for symptoms.